Andando da Magliano ad Aversa. Uno sguardo ai manicomi femminili civili e giudiziari in Italia dagli anni Trenta agli anni Cinquanta - Bianchi, Maria Rosaria (Il sogno della farfalla, 2008)
The rather ambitious aim of this article is to lead the reader to imagine the condition of psychiatric medicine, as well as the admittedly little considered or almost unknown daily life in the female wings of Italian mental hospitals, both civil and criminal, during the years 1930s-1950s. This the author endeavours to do by referring to the book The free women of Magliano, written by the Italian psychiatrist Mario Tobino in 1953, and to the material in form of photographs and various kinds of findings held in the Historical Museum set up in the Criminal Mental Hospital of Aversa, inaugurated in 1997. The author herself took part in its setting up, as at that time she worked as a psychiatrist in that institution. This circumstance enabled her to enrich her text with remarks and comments typical of a present-day woman working in the field as she reviews the past.